1992
DOI: 10.1254/jjp.59.247
|View full text |Cite
|
Sign up to set email alerts
|

Nebracetam (WEB 1881FU) Prevents N-Methyl-D-Aspartate Receptor-Mediated Neurotoxicity in Rat Striatal Slices

Abstract: ABSTRACT-The effects of nebracetam were investigated on N-methyl-D-aspartate (NMDA) receptor and voltage-operated Ca 2+ channels (VOCC)-mediated neural dysfunction by directly monitoring the real-time dynamics of dopamine released from rat striatal slices. Nebracetam (105 and 10-4 M) com pletely protected against striatal dopaminergic impairment induced by L-glutamate and NMDA, respec tively. BAY K-8644-evoked striatal dysfunction was not blocked by nebracetam (10-4 M). Therefore, nebracetam seems to produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This evidence supports our previous notion that nebracetam may be useful for the treatment of hypoxic/ischemic brain injury (8,9).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This evidence supports our previous notion that nebracetam may be useful for the treatment of hypoxic/ischemic brain injury (8,9).…”
Section: Introductionsupporting
confidence: 91%
“…Excessive Ca 2+ entry, an etiological event of neuronal injury, occurs largely through Ca 21 channels gated by the N-methyl-D-aspartate (NMDA) receptor, a subtype of the glutamate receptor, but also through voltage-gated Ca 21 channels (VGCC) (14). Nebracetam induced significant recovery from striatal dopaminergic impairment induced by L-glutamate and NMDA, but did not protect against that induced by BAY K 8644, an L-type VGCC agonist (9). These findings suggested that nebracetam possessed the ability to protect against striatal dysfunction by inhibiting an inappropriate Ca2+ influx through NMDA receptor-gated Ca 21 channels.…”
Section: Introductionmentioning
confidence: 99%